Time Zones and Periodic Intra-Industry Trade - Toru Kikuchi; Sugata Marjit (Economics and Econometrics Research Institute (EERI), 2010)
An important source of trade with time zone differences is related to the “coincidence in time” aspect of service transactions. Trade across different time zones is gainful when fulfilling nighttime demand in one time zone by utilizing daytime supply in another time zone. This note emphasizes that, due to communications revolutions, new versions of periodic intra-industry trade based on the differences in time zones emerge.
Keywords: F12; 330; Communications Nteworks; Time Zone Differences; Periodic Intra-Industry Trade